Captives and Refugees. The Forced Migration of the Inhabitants of the Byzantine Eastern Frontier during the 5th–7th Centuries in Light of Byzantine-Slavic Hagiographical Texts - Brzozowska, Zofia A. (Studia Ceranea, 2021)
This article is devoted to the image of a social situation in the eastern parts of the Byzantine Empire during the 5th–7th century, which is to be found in the East Christian hagiographical texts. They cannot be treated as a completely reliable source of information, due to exaggerations and simplifications typical for the genre. On the other hand, they testify a long-lasting and vital literary tradition – they were circulating in the Byzantine Commonwealth during the Middle Ages, were translated to several languages (inter alia to the Church Slavic). They formed the basis for stereotypes – specific for the Medieval European imagination – that the eastern frontier of the Empire was rather dangerous territory, its neighbors (Persians, Arabs) were unpredictable pagans and the Christian inhabitants of the region ought to be called their innocent victims.